PERBEDAAN TINGKAT NYERI PADA PASIEN KRITIS DI ICU YANG TERPASANG VENTILATOR MEKANIK PADA PASIEN DENGAN GANGGUAN NEUROLOGI SEBAGAI PENYAKIT DASARNYA: LITERATURE REVIEW - Diah Pujiastuti (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Critically ill patients with neurological disorders who are on mechanical ventilation face unique challenges in pain assessment and management due to limitations in verbal communication and changes in level of consciousness. This literature review to identify and analyze differences in pain levels among critically ill ICU patients on mechanical ventilation, particularly those with underlying neurological disorders, through a systematic review. The literature review utilized the PubMed, CINAHL, and Google Scholar databases for articles published between 2020 and 2025. Keywords used: pain assessment, critically ill patients, mechanical ventilation, neurological disorders, ICU. Studies indicate that patients with neurological disorders exhibit different pain behaviors (atypical behaviors) compared to general ICU patients. CPOT and BPS have been shown to be valid for pain assessment in this population. Patients with traumatic brain injury exhibit atypical behaviors such as tears, facial flushing, and yawning. The prevalence of moderate to severe pain reaches 40–70% in patients on mechanical ventilation. There are significant differences in pain manifestations and assessment between neurological and non-neurological patients in the ICU who are on mechanical ventilation. Assessment instruments specifically adapted for the neurological population, such as the CPOT, are needed to improve the accuracy of pain detection.